# Hyperbola, Parabola, Non-Linear Equations (ASAP)

Need ASAP. Due in a couple hours.

**Math 1503 Algebra**

**Homework Assignment #6**

**Due Date: Beginning of Class Wednesday, March 7**

**Chapter 10: Exercise Set 10.3 page 760**

Practice problems:

1, 5, 9, 17, 23, 27, 33

Solved Problems

18, 28, 34

Homework Problems

A) Find the vertices and use them with asymptotes to graph the equation

B) Determine the domain and range of the equation .

**Chapter 10: Exercise Set 10.4 page 771**

Practice problems:

1, 3, 5, 9, 13, 17, 19, 23, 33, 41, 43 47, 53,

Solved Problems

6, 18, 26, 38, 50

Homework Problems

C) Find the vertex and then graph the parabola .

D) Find the vertex of the parabola .

E) Use the vertex and the intercepts to sketch the parabola by choosing y values on each side of the axis of symmetry.

F) Identify each equation as a circle, ellipse, hyperbola or parabola.

a.

b.

c.

d.

e.

**Chapter 10: Exercise Set 10.5 page 782**

Practice problems:

1, 5, 11 15, 19, 21, 27, 31, 33, 37, 39

Solved Problems

16, 28, 36, 40

Homework Problems

G)

Solve this system of equations using the substitution method.

H)

Solve this system of equations using the addition method.

Extra Credit

I)

Suppose that we are designing the path of a moving camera. We choose to have it move in a hyperbola. We know that far away the path for the camera will follow the line . As it travels, we will be pointing the camera at focus of the hyperbola which is at (5,0). What is the equation of the hyperbola?

x = y−1( )

2

+3

x=y-1

()

2

+3

x =3y2 −10y−2

x=3y

2

-10y-2

x = −y2 +4y+1

x=-y

2

+4y+1

x2

3

= −

2y2

3

−3

x

2

3

=-

2y

2

3

-3

2 2x+1( )

2

−2y+ x =1+ 2y−3( )

2

22x+1

()

2

-2y+x=1+2y-3

()

2

9y2

5

−1= 9y

5

−

4×2

5

9y

2

5

-1=

9y

5

–

4x

2

5

3x−4= 2x+ 3y

2

2

−2x+2

3x-4=2x+

3y

2

2

-2x+2

y2

2

+ x2 +3= x+ x

2

2

y

2

2

+x

2

+3=x+

x

2

2

x2

2

+

y2

3

=1

y−2 =3x

x

2

2

+

y

2

3

=1

y-2=3x

3y2 − x2 =12

2×2 − y = 2

3y

2

-x

2

=12

2x

2

-y=2

y =

4x

3

y=

4x

3

2×2

9

− y2 = 9

2x

2

9

-y

2

=9

y2

4

−

x2

9

= 4

y

2

4

–

x

2

9

=4